REGULASI DIRI INTERPERSONAL UNTUK MENINGKATKAN MOTIVASI MENGHAFAL AL-QUR’AN MAHASANTRI PUTRI PPTQ AL-ASY’ARIYYAH KALIBEBER, WONOSOBO - Fathia Choirani; Muchotob Hamzah; Hidayatu Munawaroh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine interpersonal self-regulation and motivation to memorize the Qur’an in female students of PPTQ Al-Asy’ariyyah Kalibeber, Wonosobo, increasing motivation to memorize based on interpersonal self-regulation, as well as supporting and inhibiting factors. Qualitative methods with interviews, observations, and documentation were used. The results show interpersonal self-regulation is reflected in the ability to manage harmonious relationships, assertive communication, and acceptance of positive feedback that creates emotional support. Multidimensional memorization motivation, supported by time management and a competitive atmosphere, makes 91.7% of mahasantri have good memorization. Interpersonal self-regulation plays an important role in maintaining motivation through intense social interactions and structured tahfidz programs, with 95.83% of mahasantri being highly motivated. Supporting factors include personal determination, cottage environment, role models, family support and coaches, while inhibitors include lack of open communication, emotional burden, difficulty memorizing, and unsupportive environment. In conclusion, interpersonal self-regulation and environmental support are effective in increasing motivation to memorize the Qur’an.